2020
DOI: 10.1155/2020/8403192
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells between Preeclampsia and Normal Pregnant Women

Abstract: Preeclampsia is a syndrome characterized by deterioration of either the maternal condition or the fetal condition. The adverse intrauterine environment made by preeclampsia results into intrauterine growth restriction and increased risk of a variety of diseases in future life. Given the adverse environment of fetal circulation made in the preeclamptic condition, and the role of mesenchymal stem cell (MSC) as a multipotent progenitor cell, we hypothesized that MSCs derived from human umbilical cord blood (hUCB-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Recent studies have found that MSCs dysfunction is associated with the pathogenesis of PE. Human UC-MSCs (hUC-MSCs) obtained from PE women showed elevated ROS levels, decreased telomerase activity, and elevated expression of senescence-related genes (DEGs) ( 24 , 34 ). JunB and Cyclin-D1 are key cell cycle-related modulators.…”
Section: Mesenchymal Stem Cells Dysfunction In Preeclampsiamentioning
confidence: 99%
“…Recent studies have found that MSCs dysfunction is associated with the pathogenesis of PE. Human UC-MSCs (hUC-MSCs) obtained from PE women showed elevated ROS levels, decreased telomerase activity, and elevated expression of senescence-related genes (DEGs) ( 24 , 34 ). JunB and Cyclin-D1 are key cell cycle-related modulators.…”
Section: Mesenchymal Stem Cells Dysfunction In Preeclampsiamentioning
confidence: 99%
“…It is widely accepted that the placenta plays a major role in the dysregulation of the pathophysiology of PE (5). This results from harmful events at the maternal-fetal interface, including significant releases of anti-angiogenic and inflammatory factors, as well as oxidative and endoplasmic reticulum (ER) stress (6,7).…”
Section: Introductionmentioning
confidence: 99%